INFORMATION SYSTEMS DESIGN OF TOURIST ATTRACTION IN BANDAR LAMPUNG CITY - Devi Kathina Rani (Proceeding International Conference on Information Technology and Business, 2016)
Tourism is one of the selling point that Bandar Lampung City has. The information about the location of tourist attraction and the supporting facility was given in booklet and tourism map. The information distribution through those media haven’t use the technology that appropriate to the current development.Some research methods were used in this research such as, data collection methods and system design methods. The data collection methods were done in several ways such as interview with the respondents, literature study and observation. The system design methods use UML (Unified Modelling Language).The output from this research is a design of geographic information system that interactive with the user and able to attract the tourist attention to visit Bandar Lampung City and the tourist attraction. With this design hopefully can bring more information about a tourist attraction in Bandar Lampung City and gain more tourist to visit Bandar Lampung City. KEY WORDSGeographic Information System, Design, Tourism